The Relationship Between Self Concept, Social Support, and Psychological Well-being of Empty-nest Elderly - Ardina Mispa Uji Mar’atussolikha; Lita Heni Kusumawardani; Koernia Nanda Pratama (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2025)
Introduction: The aging process in the elderly includes changes in physical appearance, health conditions, cognitive function, social-emotional function, and interpersonal relationships. On elderly who live alone or are called empty-nest elderly this can encourage changes in an individual's views and attitudes towards themselves, as well as support from other people received by the elderly, which can give rise to psychological phenomena in the form of feelings of sadness, loss, and loneliness which are often not realized. Objectives: This study aims to determine the relationship between self-concept and social support on the psychological well-being of empty-nest elderly. Methods: This research is a quantitative study with a cross-sectional design using a purposive random sampling technique with a total of 108 empty-nest elderly as respondents. The data were analyzed using the Sommers'd Gamma test. Results: The results of the research show that there is a significant relationship between self-concept and psychological well-being (memengaruhi=0.048, p<0.05) with a moderate degree of correlation (coefficient r=0.362) and a significant relationship to social support (memengaruhi=0.003, p<0.05) with a strong degree of correlation (coefficient r=0.548). Conclusions: Self-concept and social support have a significant influence on the psychological well-being of elderly empty nesters, therefore it is hoped that society can facilitate elderly people to have a good self-concept and provide strong social support to increase the level of psychological well-being of empty-nest elderly.